Optimization of E-Learning Learning at Vocational School in Selatan Minahasa (Case Study at North Sulawesi Shipping Polytechnic) - Muhammad Haeruddin Syam; Jolanda Altje Meiske Rawis; Roos Marie Stella Tuerah; Mozes Markus Wullur (Researchparks Publishing, 2022)
The development of information technology has entered various aspects of life, including the world of education, especially learning, which has been intervened by the existence of this technology. Along with the development of information technology applications in the world of education, various learning materials have been produced and consumed by learners through the medium of information technology in various packaging forms. In contrast to the traditional learning process, which relies on the teacher as the first and main source of learning, other sources are only complementary to learning activities. This research was carried out at the shipping Polytechnic in North Sulawesi in 2021. The methodology used is qualitative as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. This approach is directed at the background of the individual holistically (whole). The data analysis technique used in this study refers to the concept of Milles & Huberman. Based on the research results are North Sulawesi Shipping Polytechnic in order to remain consistent in planning for optimizing learning, so that teaching and learning activities can be realized as expected, North Sulawesi Shipping Polytechnic always strives to improve the implementation of teaching and learning processes or activities, such as increasing the ability of lecturers or teachers in the field of technology and applying it to participants educate. Evaluations or obstacles faced during practical learning using e-learning applications so that they are improved and their quality is improved.